Flow guide method of functional current collector
By treating the copper layer and active substances on the surface of the PET base film and impregnating the conductive glue liquid at the pole ear position to form a functional current collector, the complex problem of current collector contact processing in traditional battery manufacturing processes is solved, and efficient current transmission and simplified manufacturing processes are achieved.
Patent Information
- Application Number
- CN202411885511.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
In traditional battery manufacturing processes, the contact processing of current collectors is complicated, which increases manufacturing costs and may lead to process instability.
After sputtering a copper layer on the surface of the PET base film and a copper layer plating electrolyte on the surface of the copper layer, the conductive glue solution is directly immersed in the uncoppered pole ear to form an electrode sheet, and a functional current collector is obtained by high temperature and high pressure treatment.
The contact resistance inside the battery is reduced, the charging and discharging efficiency and power density are improved, the manufacturing process is simplified, the manufacturing cost is reduced, and the battery utilization is improved.
Smart Images

Figure CN119674096A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of current collectors, in particular to a flow guiding method for a functional current collector. Background Art
[0002] The current collector plays a vital role in modern battery technology. With the continuous advancement of science and technology and the increasing demand for batteries, the modern value of the current collector has become increasingly significant. The core value of the current collector lies in its current transmission function in the battery. As the carrier of internal charge in the battery, the current collector is responsible for effectively transferring the charge generated by the active materials of the battery to the external circuit. High-quality current collectors can significantly reduce the contact resistance of the battery and improve the energy conversion efficiency of the battery. This efficient current transmission not only enhances the power density of the battery, but also improves the charge and discharge performance of the battery, making it perform better in high-performance application scenarios. However, in traditional battery manufacturing processes, the contact processing of the current collector often involves complex welding and connection steps, which not only increase manufacturing costs, but may also lead to process instability.
[0003] In order to overcome the defects of the prior art, the present invention provides a method for guiding a functional current collector. Summary of the invention
[0004] The object of the present invention is to provide a flow guiding method for a functional current collector to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A functional current collector comprises the following steps: firstly sputtering a 50-80nm copper layer on the surface of a PET base film, electroplating a 1.0-1.5μm copper layer with water, then coating the surface of the copper layer with active material, and then directly dipping a conductive glue into the uncopper-plated pole ear position to obtain a pole piece; stacking a plurality of pole pieces together, inserting a current collector into the center of the stack, and subjecting the pole pieces to high temperature and high pressure treatment to obtain a functional current collector.
[0007] More optimally, the dipping parameters are: immersing the pole ear in the conductive glue and standing at -95Mpa for 2-5min. This step can evenly adhere the conductive glue to the edge of the pole ear and the inside of the gap, so as to achieve the purpose of conduction on both sides of the pole ear; the active material is composed of 93wt% graphite, 2wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose, and 3wt% styrene-butadiene rubber; the conductive glue is composed of monovinyl-terminated polydimethylsiloxane (30-65wt%), triethylsilane (5-10wt%), dimethyl silicone oil (5-30wt%) and a platinum complex catalyst with a platinum content of 800PPM (0.01-0.2wt%), silver powder and copper powder (5-20wt%) with an average particle size of 50-200nm, and trimethylbenzene (5-30wt%); high temperature and high pressure treatment parameters: temperature is 150-160℃, pressure is 500-520MPa, and time is 3-5min.
[0008] More optimally, the preparation process of the PET base film is as follows: S1: Mix multi-walled carbon nanotubes and 95-98% concentrated sulfuric acid and stir for 6-8h, then add 65-70% concentrated nitric acid and continue stirring and reacting for 30-40min, after stirring, reflux at 120-140°C for 40-60min, after the reaction, dilute, filter, wash to neutrality, and vacuum dry to obtain pretreated carbon nanotubes; mix the pretreated carbon nanotubes and thionyl chloride, ultrasonically disperse for 1-2h, reflux for reaction under nitrogen environment for 20-25h, and then obtain acyl chloride carbon nanotubes by reduced pressure distillation;
[0009] S2: mixing acyl chloride carbon nanotubes, silicon polymer and 1,4-dioxane, and ultrasonically dispersing for 2-4 hours to obtain a dispersion; in a nitrogen environment, mixing polyethylene terephthalate, 1,2-dichloroethane and trifluoroacetic acid, stirring and reacting at 25-30°C for 2-3 hours, and then adding the dispersion dropwise, stirring and reacting in an oil bath at 80-90°C for 45-50 hours after the addition, and filtering under reduced pressure, washing and drying to obtain modified carbon nanotubes;
[0010] S3: dissolving the modified carbon nanotubes in tetrahydrofuran, ultrasonically dispersing for 2-4h, then adding oxycarbonyl-4-hydroxyaniline, reflux reaction at 60-70°C in a nitrogen environment for 12-15h, then adding trifluoroacetic acid and dichloromethane and stirring the mixture for 1-2h, after the reaction is completed, washing by centrifugation, and freeze-drying to obtain amino carbon nanotubes; mixing the amino carbon nanotubes with 1.0-1.5mol / L hydrochloric acid solution, ultrasonically dispersing for 30-40min, then treating in an ice-water bath to a temperature of 0-2°C, then adding aniline monomer and stirring for 20-30min, then dropping ammonium persulfate solution and continuing the reaction for 6-8h, after the reaction is completed, washing, and freeze-drying to obtain composite carbon nanotubes;
[0011] S4: PET resin, composite carbon nanotubes, surfactant and coupling agent are uniformly mixed to obtain a composite material, and after standing for 8-12 hours, the composite material is melt-extruded, cast, cast and biaxially stretched to obtain a PET base film.
[0012] More optimally, in step S1, the reaction mass ratio of the pretreated carbon nanotubes to thionyl chloride is (0.5-0.7):65.
[0013] More optimally, in step S2, the contents of the components of the modified carbon nanotubes are: by mass, 20-25 parts of chlorinated carbon nanotubes, 3-4 parts of silicon polymer, 100-150 parts of 1,4-dioxane, 10-14 parts of polyethylene terephthalate, 5-6 parts of 1,2-dichloroethane, and 5-6 parts of trifluoroacetic acid.
[0014] More optimally, the preparation process of the silicon polymer is as follows: sodium hydroxide powder and deionized water are mixed, ultrasonically dispersed for 30-40 minutes, silicon dioxide powder is added to react for 3-4 hours, 35-38% hydrochloric acid solution, tetrahydrofuran and sodium chloride are added, and the reaction is continued for 30-40 minutes. After the reaction is completed, the organic layer is allowed to stand for dehydration, suction filtration and distillation to obtain silicon polymer; the content of each component of the silicon polymer is: in parts by mass, 1.0-1.2 parts of sodium hydroxide powder, 60-70 parts of deionized water, 3.0-3.5 parts of silicon dioxide powder, 65-70 parts of hydrochloric acid solution, 160-180 parts of tetrahydrofuran and 36-40 parts of sodium chloride.
[0015] More optimally, in step S3, when preparing the amino-modified carbon nanotubes, the reaction mass ratio of the main reactants, the modified carbon nanotubes and oxycarbonyl-4-hydroxyaniline, is 4:(1.0-1.5).
[0016] More optimally, in step S3, the reaction mass ratio of the amination carbon nanotubes, the aniline monomer and the ammonium persulfate is (0.02-0.03):6:3.
[0017] More optimally, in step S4, the contents of the components of the composite material are: by mass, 75-85 parts of PET resin, 20-30 parts of composite carbon nanotubes, 0.5-0.7 parts of surfactant, and 0.5-0.7 parts of coupling agent; the surfactant is sodium dodecylbenzene sulfonate, and the coupling agent is γ-aminopropyltriethoxysilane.
[0018] A method for conducting current of a functional current collector comprises the following steps: a lithium-ion battery prepared by the functional current collector comprises the following steps: assembling a positive current collector and a positive active material layer into a positive electrode, assembling a functional current collector and a negative active material layer into a negative electrode, assembling the positive electrode and the negative electrode into a battery, then selecting an aluminum-plastic film shell for packaging and molding, and performing electrolyte injection, aging, formation, and volume separation to obtain a lithium-ion battery.
[0019] Beneficial effects of the present invention:
[0020] The present invention sequentially performs oxidation treatment, chlorination treatment, modification treatment, amination treatment, and graft polymerization treatment on multi-walled carbon nanotubes to obtain composite carbon nanotubes with good mechanical properties and conductive properties. Then, PET resin, composite carbon nanotubes, surfactants, and coupling agents are uniformly mixed, and the PET base film is obtained by standing, melt extrusion, casting, sheet casting, and biaxial stretching. The present invention sequentially sputters a copper layer and electroplates a copper layer on the surface of the PET base film, then coats the surface of the copper layer with active substances, and then directly impregnates the uncoppered pole ear position with conductive glue to obtain a pole piece; multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack to obtain a functional current collector.
[0021] The characteristic of the present invention is that, in step S1, the present invention performs oxidation treatment on multi-walled carbon nanotubes by adding concentrated sulfuric acid and concentrated nitric acid to obtain pretreated multi-walled carbon nanotubes with a variety of oxygen-containing groups. Then the pretreated multi-walled carbon nanotubes and thionyl chloride are mixed and reacted to obtain chlorinated carbon nanotubes. The chlorinated carbon nanotubes prepared by the present invention contain a large number of acyl chloride groups on their surfaces, so in step S2, the silicon polymer containing silanol groups and the polyethylene terephthalate containing terminal hydroxyl groups can undergo esterification reaction with the chlorinated carbon nanotubes to obtain modified carbon nanotubes. On the one hand, this step can significantly improve the corrosion resistance, high temperature resistance and mechanical strength of multi-walled carbon nanotubes by introducing silicon polymers, and on the other hand, this step pre-introduces the polyethylene terephthalate component, which can effectively improve the compatibility of carbon nanotubes and PET resin when the PET base film is subsequently prepared.
[0022] The feature of the present invention is that in step S3, modified carbon nanotubes, oxycarbonyl-4-hydroxyaniline, trifluoroacetic acid and dichloromethane are mixed, an amination reaction occurs, and amino carbon nanotubes are prepared. Aminated carbon nanotubes, hydrochloric acid solution, aniline monomer and ammonium persulfate solution are then mixed, a graft polymerization reaction occurs, and a polyaniline conductive layer is introduced on the surface of the carbon nanotubes, i.e., composite carbon nanotubes. In summary, the composite carbon nanotubes prepared by the present invention have excellent electrical conductivity, can significantly enhance the overall electrical conductivity of the functional current collector, and make the current transmission in electric energy storage devices such as batteries and supercapacitors more efficient. In addition, the introduction of composite carbon nanotubes can improve the mechanical strength and toughness of the functional current collector, reduce the risk of mechanical damage during operation, and improve the durability and reliability of the product. Therefore, the functional current collector prepared by adding composite carbon nanotubes also has good electrical conductivity and mechanical properties.
[0023] In terms of process, the present invention directly immerses the uncopper-plated pole ear position into a conductive glue to obtain a pole piece; then it is cured by rapid high-temperature baking, and the pole ear is shaped by hot pressing, and finally connected to an external conductive metal to lead out the current. After the present invention uses conductive glue to drain, it can effectively reduce the contact resistance inside the battery. Low contact resistance helps to improve the battery's charging and discharging efficiency and power density, thereby improving the overall performance of the battery. Compared with traditional transfer welding, the application of conductive glue only requires a hot pressing process, without the need for an additional transfer welding process. This not only reduces manufacturing time, but also reduces manufacturing complexity and improves the battery's availability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0025] Figure 1 It is a structural diagram of the functional current collector of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Source of raw materials:
[0028] Multi-walled carbon nanotubes, provided by Guangzhou Hongwu Materials Technology Co., Ltd., have a diameter of 60 nm and a tube length of 2 μm; polyethylene terephthalate can be purchased from Yanshan Petrochemical Company with a specification of intrinsic viscosity 0.63; PET resin can be purchased from Shanghai Heyiyuan Plastic Raw Materials Co., Ltd. with a specification of 25 mm; monovinyl-terminated polydimethylsiloxane can be purchased from Wuhan Kemeiwo Chemical Co., Ltd., CAS No.: 68083-19-2; triethylsilane, CAS No. 617-86-7; dimethyl silicone oil can be purchased from Laiyang Shengbang Silicone Technology Co., Ltd., model SI-201; platinum complex catalyst can be purchased from Jining Fangyu Chemical Co., Ltd.; in terms of mass parts, one portion is 1 g.
[0029] Example 1: S1: Mix multi-walled carbon nanotubes and 98% concentrated sulfuric acid and stir for 8 hours, then add 70% concentrated nitric acid and continue stirring and reacting for 40 minutes, after stirring, reflux at 140°C for 60 minutes, after the reaction, dilute, filter, wash to neutrality, and vacuum dry to obtain pretreated carbon nanotubes; mix the pretreated carbon nanotubes and thionyl chloride, ultrasonically disperse for 2 hours, then reflux for reaction under nitrogen environment for 25 hours, and then distill under reduced pressure to obtain acyl chloride carbon nanotubes; the reaction mass ratio of the pretreated carbon nanotubes and thionyl chloride is 0.5:65;
[0030] S2: 1g of sodium hydroxide powder and 60g of deionized water were mixed, ultrasonically dispersed for 40min, and then 3g of silicon dioxide powder was added to react for 4h, and then 65g of 38% hydrochloric acid solution, 160g of tetrahydrofuran, and 36g of sodium chloride were added, and the reaction was continued for 40min. After the reaction was completed, the organic layer was allowed to stand for dehydration, suction filtration, and distillation to obtain a silicon polymer;
[0031] 20g of acyl chloride carbon nanotubes, 3g of silicon polymer and 100g of 1,4-dioxane were mixed and ultrasonically dispersed for 4h to obtain a dispersion; under a nitrogen environment, 10g of polyethylene terephthalate, 5g of 1,2-dichloroethane and 5g of trifluoroacetic acid were mixed, stirred and reacted at 30°C for 3h, and then the dispersion was added dropwise. After the addition was completed, the mixture was stirred and reacted in an oil bath at 90°C for 50h. After the reaction was completed, the modified carbon nanotubes were obtained by filtration under reduced pressure, washing and drying;
[0032] S3: The modified carbon nanotubes were dissolved in tetrahydrofuran, ultrasonically dispersed for 4 hours, and then 4-hydroxyaniline was added. The mixture was refluxed at 70°C for 15 hours under a nitrogen environment, and then trifluoroacetic acid and dichloromethane were added and stirred for 2 hours. After the reaction, the mixture was centrifuged, washed, and freeze-dried to obtain the amino carbon nanotubes. The amino carbon nanotubes were mixed with 1.5 mol / L hydrochloric acid solution, ultrasonically dispersed for 40 minutes, and then treated in an ice-water bath until the temperature reached 2°C. Then, aniline monomer was added and stirred for 30 minutes, and then ammonium persulfate solution was added dropwise to continue the reaction for 8 hours. After the reaction, the mixture was washed and freeze-dried to obtain the composite carbon nanotubes. The reaction mass ratio of the modified carbon nanotubes and 4-hydroxyaniline was 4:1.5; the reaction mass ratio of the amino carbon nanotubes, aniline monomer, and ammonium persulfate was 0.02:6:3.
[0033] S4: 75 g of PET resin, 20 g of composite carbon nanotubes, 0.5 g of sodium dodecylbenzene sulfonate and 0.5 g of γ-aminopropyltriethoxysilane were uniformly mixed to obtain a composite material, and after standing for 12 hours, the composite material was melt-extruded, cast, cast, and biaxially stretched to obtain a PET base film;
[0034] S5: First, a 50nm copper layer is sputtered on the surface of the PET base film, and then a 1μm copper layer is electroplated with water, and then an active material is coated on the surface of the copper layer, and then the uncopper-plated ear position is directly immersed in a conductive adhesive, and allowed to stand at -95Mpa for 5 minutes to obtain a pole piece; multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack, and a functional current collector is obtained after high temperature and high pressure treatment; the active material is composed of 93wt% graphite, 2wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose, and 3wt% styrene-butadiene rubber; the conductive adhesive is composed of monovinyl-terminated polydimethylsiloxane (50wt%), triethylsilane (8wt%), dimethyl silicone oil (15wt%), a platinum complex catalyst with a platinum content of 800PPM (0.1wt%), silver powder with an average particle size of 100nm (10wt%), and trimethylbenzene (16.9wt%); high temperature and high pressure treatment parameters: temperature is 150°C, pressure is 500MPa, and time is 3min.
[0035] Example 2: S1: Mix multi-walled carbon nanotubes and 96% concentrated sulfuric acid and stir for 7 hours, then add 67% concentrated nitric acid and continue stirring and reacting for 35 minutes. After the stirring, reflux at 130°C for 50 minutes. After the reaction, dilute, filter, wash to neutrality, and vacuum dry to obtain pretreated carbon nanotubes; mix the pretreated carbon nanotubes and thionyl chloride, ultrasonically disperse for .5 hours, reflux under nitrogen environment for 23 hours, and then distill under reduced pressure to obtain acyl chloride carbon nanotubes; the reaction mass ratio of pretreated carbon nanotubes to thionyl chloride is 0.5:65;
[0036] S2: 1g of sodium hydroxide powder and 60g of deionized water were mixed, ultrasonically dispersed for 35min, and then 3g of silicon dioxide powder was added to react for 3.5h, and then 65g of 36% hydrochloric acid solution, 160g of tetrahydrofuran, and 36g of sodium chloride were added, and the reaction was continued for 35min. After the reaction was completed, the organic layer was allowed to stand for dehydration, suction filtration, and distillation to obtain a silicon polymer;
[0037] 20g of acyl chloride carbon nanotubes, 3g of silicon polymer and 100g of 1,4-dioxane were mixed and ultrasonically dispersed for 3h to obtain a dispersion; under a nitrogen environment, 10g of polyethylene terephthalate, 5g of 1,2-dichloroethane and 5g of trifluoroacetic acid were mixed, stirred and reacted at 27°C for 2.5h, and then the dispersion was added dropwise. After the addition was completed, the mixture was stirred and reacted in an oil bath at 85°C for 47h. After the reaction was completed, the modified carbon nanotubes were obtained by filtration under reduced pressure, washing and drying;
[0038] S3: The modified carbon nanotubes were dissolved in tetrahydrofuran, ultrasonically dispersed for 3 hours, and then 4-hydroxyaniline was added. The mixture was refluxed at 65°C for 13 hours under a nitrogen environment, and then trifluoroacetic acid and dichloromethane were added and stirred for 1.5 hours. After the reaction, the mixture was centrifuged, washed, and freeze-dried to obtain the amino carbon nanotubes. The amino carbon nanotubes were mixed with 1.2 mol / L hydrochloric acid solution, ultrasonically dispersed for 35 minutes, and then treated in an ice-water bath to a temperature of 1°C, and then aniline monomer was added and stirred for 25 minutes, and then ammonium persulfate solution was added dropwise to continue the reaction for 7 hours. After the reaction, the mixture was washed and freeze-dried to obtain the composite carbon nanotubes. The reaction mass ratio of the modified carbon nanotubes and 4-hydroxyaniline was 4:1.5; the reaction mass ratio of the amino carbon nanotubes, aniline monomer, and ammonium persulfate was 0.02:6:3.
[0039] S4: 75 g of PET resin, 20 g of composite carbon nanotubes, 0.5 g of sodium dodecylbenzene sulfonate and 0.5 g of γ-aminopropyltriethoxysilane were uniformly mixed to obtain a composite material, and after standing for 10 hours, the composite material was melt-extruded, cast, cast, and biaxially stretched to obtain a PET base film;
[0040] S5: First, a 50nm copper layer is sputtered on the surface of the PET base film, and then a 1μm copper layer is electroplated with water, and then an active material is coated on the surface of the copper layer, and then the uncopper-plated pole ear position is directly immersed in a conductive adhesive, and allowed to stand for 3 minutes at -95Mpa to obtain a pole piece; multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack, and a functional current collector is obtained by high temperature and high pressure treatment; the active material is composed of 93wt% graphite, 2wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose, and 3wt% styrene-butadiene rubber; the conductive adhesive is composed of monovinyl-terminated polydimethylsiloxane (50wt%), triethylsilane (8wt%), dimethyl silicone oil (15wt%), a platinum complex catalyst with a platinum content of 800PPM (0.1wt%), silver powder with an average particle size of 100nm (10wt%), and trimethylbenzene (16.9wt%); high temperature and high pressure treatment parameters: temperature is 150°C, pressure is 500MPa, and time is 3min.
[0041] Example 3: S1: Mix multi-walled carbon nanotubes and 95% concentrated sulfuric acid and stir for 6 hours, then add 65% concentrated nitric acid and continue stirring and reacting for 30 minutes, after stirring, reflux at 120°C for 40 minutes, after the reaction, dilute, filter, wash to neutrality, and vacuum dry to obtain pretreated carbon nanotubes; mix the pretreated carbon nanotubes and thionyl chloride, ultrasonically disperse for 1 hour, reflux for reaction under nitrogen environment for 20 hours, and then distill under reduced pressure to obtain acyl chloride carbon nanotubes; the reaction mass ratio of pretreated carbon nanotubes to thionyl chloride is 0.5:65;
[0042] S2: 1g of sodium hydroxide powder and 60g of deionized water were mixed, ultrasonically dispersed for 30min, and then 3g of silicon dioxide powder was added to react for 3h, and then 65g of 35% hydrochloric acid solution, 160g of tetrahydrofuran, and 36g of sodium chloride were added, and the reaction was continued for 30min. After the reaction was completed, the organic layer was allowed to stand for dehydration, suction filtration, and distillation to obtain a silicon polymer;
[0043] 20g of acyl chloride carbon nanotubes, 3g of silicon polymer and 100g of 1,4-dioxane were mixed and ultrasonically dispersed for 2h to obtain a dispersion; under a nitrogen environment, 10g of polyethylene terephthalate, 5g of 1,2-dichloroethane and 5g of trifluoroacetic acid were mixed and stirred at 25°C for 2h, and then the dispersion was added dropwise. After the addition was completed, the mixture was stirred in an oil bath at 80°C for 45h. After the reaction was completed, the modified carbon nanotubes were obtained by filtration under reduced pressure, washing and drying;
[0044] S3: The modified carbon nanotubes were dissolved in tetrahydrofuran, ultrasonically dispersed for 2 hours, and then 4-hydroxyaniline was added. The mixture was refluxed at 60°C for 12 hours under a nitrogen environment, and then trifluoroacetic acid and dichloromethane were added and stirred for 1 hour. After the reaction, the mixture was centrifuged, washed, and freeze-dried to obtain the amino carbon nanotubes. The amino carbon nanotubes were mixed with 1.0 mol / L hydrochloric acid solution, ultrasonically dispersed for 30 minutes, and then treated in an ice-water bath until the temperature was 0°C. Then, aniline monomer was added and stirred for 20 minutes, and then ammonium persulfate solution was added dropwise to continue the reaction for 6 hours. After the reaction, the mixture was washed and freeze-dried to obtain the composite carbon nanotubes. The reaction mass ratio of the modified carbon nanotubes and 4-hydroxyaniline was 4:1.5; the reaction mass ratio of the amino carbon nanotubes, aniline monomer, and ammonium persulfate was 0.02:6:3.
[0045] S4: 75 g of PET resin, 20 g of composite carbon nanotubes, 0.5 g of sodium dodecylbenzene sulfonate and 0.5 g of γ-aminopropyltriethoxysilane were uniformly mixed to obtain a composite material, and after standing for 8 hours, the composite material was melt-extruded, cast, cast, and biaxially stretched to obtain a PET base film;
[0046] S5: First, a 50nm copper layer is sputtered on the surface of the PET base film, and then a 1μm copper layer is electroplated with water, and then an active material is coated on the surface of the copper layer, and then the uncopper-plated pole ear position is directly immersed in a conductive adhesive, and allowed to stand at -95Mpa for 2min to obtain a pole piece; multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack, and subjected to high temperature and high pressure treatment to obtain a functional current collector; the active material is composed of 93wt% graphite, 2wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose, and 3wt% styrene-butadiene rubber; the conductive adhesive is composed of monovinyl-terminated polydimethylsiloxane (50wt%), triethylsilane (8wt%), dimethyl silicone oil (15wt%), a platinum complex catalyst with a platinum content of 800PPM (0.1wt%), silver powder with an average particle size of 100nm (10wt%), and trimethylbenzene (16.9wt%); high temperature and high pressure treatment parameters: temperature is 150°C, pressure is 500MPa, and time is 3min.
[0047] Comparative Example 1: Step S2 is removed, and the rest is the same as Example 1, and the specific steps are as follows: S1: Multi-walled carbon nanotubes and 98% concentrated sulfuric acid are mixed and stirred for 8 hours, and then 70% concentrated nitric acid is added and stirred for 40 minutes. After the stirring is completed, the mixture is refluxed at 140° C. for 60 minutes. After the reaction is completed, the mixture is diluted, filtered, washed to neutrality, and vacuum dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes are mixed with thionyl chloride, ultrasonically dispersed for 2 hours, and then refluxed for 25 hours under a nitrogen environment, and then distilled under reduced pressure to obtain acyl chloride carbon nanotubes; the reaction mass ratio of the pretreated carbon nanotubes to the thionyl chloride is 0.5:65;
[0048] S2: dissolving the chlorinated carbon nanotubes in tetrahydrofuran, ultrasonically dispersing for 4 hours, then adding oxycarbonyl-4-hydroxyaniline, reflux reaction at 70°C under nitrogen environment for 15 hours, then adding trifluoroacetic acid and dichloromethane and stirring the mixture for 2 hours, after the reaction, centrifugation washing and freeze drying were performed to obtain amino carbon nanotubes; the amino carbon nanotubes were mixed with 1.5 mol / L hydrochloric acid solution, ultrasonically dispersed for 40 minutes, then treated in an ice-water bath to a temperature of 2°C, then adding aniline monomer and stirring for 30 minutes, then dropping ammonium persulfate solution and continuing the reaction for 8 hours, after the reaction, washing and freeze drying were performed to obtain composite carbon nanotubes; the reaction mass ratio of chlorinated carbon nanotubes and oxycarbonyl-4-hydroxyaniline was 4:1.5; the reaction mass ratio of amino carbon nanotubes, aniline monomer and ammonium persulfate was 0.02:6:3;
[0049] S3: 75g PET resin, 20g composite carbon nanotubes, 0.5g sodium dodecylbenzene sulfonate and 0.5g γ-aminopropyltriethoxysilane were uniformly mixed to obtain a composite material, and after standing for 12 hours, the composite material was melt-extruded, cast, cast, and biaxially stretched to obtain a PET base film;
[0050] S4: First, a 50nm copper layer is sputtered on the surface of the PET base film, and then a 1μm copper layer is electroplated with water, and then an active material is coated on the surface of the copper layer, and then the uncopper-plated pole ear position is directly immersed in a conductive adhesive, and allowed to stand at -95Mpa for 5 minutes to obtain a pole piece; multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack, and a functional current collector is obtained after high temperature and high pressure treatment; the active material is composed of 93wt% graphite, 2wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose, and 3wt% styrene-butadiene rubber; the conductive adhesive is composed of monovinyl-terminated polydimethylsiloxane (50wt%), triethylsilane (8wt%), dimethyl silicone oil (15wt%), a platinum complex catalyst with a platinum content of 800PPM (0.1wt%), silver powder with an average particle size of 100nm (10wt%), and trimethylbenzene (16.9wt%); high temperature and high pressure treatment parameters: temperature is 150°C, pressure is 500MPa, and time is 3min.
[0051] Comparative Example 2: Step S3 is removed, and the rest is the same as Example 1, and the specific steps are as follows: S1: Multi-walled carbon nanotubes and 98% concentrated sulfuric acid are mixed and stirred for 8 hours, and then 70% concentrated nitric acid is added and stirred for 40 minutes. After the stirring is completed, the mixture is refluxed at 140° C. for 60 minutes. After the reaction is completed, the mixture is diluted, filtered, washed to neutrality, and vacuum dried to obtain pretreated carbon nanotubes; the pretreated carbon nanotubes are mixed with thionyl chloride, ultrasonically dispersed for 2 hours, and then refluxed for 25 hours under a nitrogen environment, and then distilled under reduced pressure to obtain acyl chloride carbon nanotubes; the reaction mass ratio of the pretreated carbon nanotubes to the thionyl chloride is 0.5:65;
[0052] S2: 1g of sodium hydroxide powder and 60g of deionized water were mixed, ultrasonically dispersed for 40min, and then 3g of silicon dioxide powder was added to react for 4h, and then 65g of 38% hydrochloric acid solution, 160g of tetrahydrofuran, and 36g of sodium chloride were added, and the reaction was continued for 40min. After the reaction was completed, the organic layer was allowed to stand for dehydration, suction filtration, and distillation to obtain a silicon polymer;
[0053] 20g of acyl chloride carbon nanotubes, 3g of silicon polymer and 100g of 1,4-dioxane were mixed and ultrasonically dispersed for 4h to obtain a dispersion; under a nitrogen environment, 10g of polyethylene terephthalate, 5g of 1,2-dichloroethane and 5g of trifluoroacetic acid were mixed, stirred and reacted at 30°C for 3h, and then the dispersion was added dropwise. After the addition was completed, the mixture was stirred and reacted in an oil bath at 90°C for 50h. After the reaction was completed, the modified carbon nanotubes were obtained by filtration under reduced pressure, washing and drying;
[0054] S3: 75 g of PET resin, 20 g of modified carbon nanotubes, 0.5 g of sodium dodecylbenzene sulfonate and 0.5 g of γ-aminopropyltriethoxysilane were uniformly mixed to obtain a composite material, and after standing for 12 hours, the composite material was melt-extruded, cast, cast and biaxially stretched to obtain a PET base film;
[0055] S4: First, a 50nm copper layer is sputtered on the surface of the PET base film, and then a 1μm copper layer is electroplated with water, and then an active material is coated on the surface of the copper layer, and then the uncopper-plated pole ear position is directly immersed in a conductive adhesive, and allowed to stand at -95Mpa for 5 minutes to obtain a pole piece; multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack, and a functional current collector is obtained after high temperature and high pressure treatment; the active material is composed of 93wt% graphite, 2wt% conductive carbon black, 2wt% sodium carboxymethyl cellulose, and 3wt% styrene-butadiene rubber; the conductive adhesive is composed of monovinyl-terminated polydimethylsiloxane (50wt%), triethylsilane (8wt%), dimethyl silicone oil (15wt%), a platinum complex catalyst with a platinum content of 800PPM (0.1wt%), silver powder with an average particle size of 100nm (10wt%), and trimethylbenzene (16.9wt%); high temperature and high pressure treatment parameters: temperature is 150°C, pressure is 500MPa, and time is 3min.
[0056] Detection test:
[0057] Tensile strength test: The PET base film prepared by the present invention is used as a sample, and the test is performed according to GB / T25255-2010 standard. The sample is measured using a universal tensile testing machine, and the test results are repeated three times to obtain an average value.
[0058] Resistivity test: The PET base film prepared by the present invention is used as a sample, and the sample is measured by a four-probe method. The sample data is substituted into the conductivity formula to obtain the conductivity. The test needs to be repeated three times to obtain the average value. The results are as follows:
[0059] <![CDATA[Tensile strength / MPa > Conductivity / (S / m) Example 1 308 <![CDATA[5.7×10 13 ]]> Example 2 306 <![CDATA[5.6×10 13 ]]> Example 3- 303 <![CDATA[5.5×10 13 ]]> Comparative Example 1 263 <![CDATA[5.5×10 13 ]]> Comparative Example 2 306 <![CDATA[4.3×10 13 ]]>
[0060] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that there is no obvious fluctuation in the performance of the samples.
[0061] Comparative Example 1: Step S2 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the tensile strength is reduced to 263 MPa. The reason is analyzed as follows: after step S2 is removed, the silicon polymer and polyethylene terephthalate components will be removed from the carbon nanotubes accordingly, so the mechanical properties of the prepared PET base film sample will be reduced, so the tensile strength is reduced.
[0062] Comparative Example 2: Step S3 is removed, and the rest is the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the conductivity is reduced to 4.3×10 13 The reason is analyzed as follows: after removing step S3, the polyaniline conductive component will be correspondingly removed from the carbon nanotubes, so the conductive performance of the prepared PET base film sample will be reduced, so the conductivity is reduced.
[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0064] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A functional current collector, characterized in that: The following steps are involved: First, a 50-80nm copper layer is sputtered on the surface of the PET base film, and a 1.0-1.5μm copper layer is electroplated with water. Then, active material is coated on the surface of the copper layer. Then, the uncopper-plated ear position is directly immersed in a conductive glue to obtain a pole piece. Multiple pole pieces are stacked together, and a current collector is inserted into the center of the stack. After high temperature and high pressure treatment, a functional current collector is obtained.
2. A functional current collector according to claim 1, characterized in that: Impregnation parameters: immerse the tab in the conductive adhesive and let it stand at -95Mpa for 2-5 minutes. This step can evenly adhere the conductive adhesive to the edge of the tab and the inside of the gap, so as to achieve the purpose of conduction on both sides of the tab; the conductive adhesive is composed of monovinyl-terminated polydimethylsiloxane (30-65wt%), triethylsilane (5-10wt%), dimethyl silicone oil (5-30wt%) and a platinum complex catalyst with a platinum content of 800PPM (0.01-0.2wt%), silver powder and copper powder with an average particle size of 50-200nm (5-20wt%), and trimethylbenzene (5-30wt%); high temperature and high pressure treatment parameters: temperature is 150-160℃, pressure is 500-520MPa, and time is 3-5min.
3. A functional current collector according to claim 1, characterized in that: The preparation process of the PET base film is as follows: S1: multi-walled carbon nanotubes and 95-98% concentrated sulfuric acid are mixed and stirred for 6-8 hours, and then 65-70% concentrated nitric acid is added and stirred for 30-40 minutes. After the stirring is completed, the mixture is refluxed at 120-140° C. for 40-60 minutes. After the reaction is completed, the mixture is diluted, filtered, washed to neutrality, and vacuum dried to obtain pretreated carbon nanotubes; The pretreated carbon nanotubes and thionyl chloride are mixed, ultrasonically dispersed for 1-2 hours, refluxed for 20-25 hours under a nitrogen environment, and then distilled under reduced pressure to obtain acyl chloride carbon nanotubes; S2: mixing acyl chloride carbon nanotubes, silicon polymer and 1,4-dioxane, and ultrasonically dispersing for 2-4 hours to obtain a dispersion; in a nitrogen environment, mixing polyethylene terephthalate, 1,2-dichloroethane and trifluoroacetic acid, stirring and reacting at 25-30°C for 2-3 hours, and then adding the dispersion dropwise, stirring and reacting in an oil bath at 80-90°C for 45-50 hours after the addition, and filtering under reduced pressure, washing and drying to obtain modified carbon nanotubes; S3: dissolving the modified carbon nanotubes in tetrahydrofuran, ultrasonically dispersing for 2-4h, then adding oxycarbonyl-4-hydroxyaniline, reflux reaction at 60-70°C in a nitrogen environment for 12-15h, then adding trifluoroacetic acid and dichloromethane and stirring the mixture for 1-2h, after the reaction is completed, washing by centrifugation, and freeze-drying to obtain amino carbon nanotubes; mixing the amino carbon nanotubes with 1.0-1.5mol / L hydrochloric acid solution, ultrasonically dispersing for 30-40min, then treating in an ice-water bath to a temperature of 0-2°C, then adding aniline monomer and stirring for 20-30min, then dropping ammonium persulfate solution and continuing the reaction for 6-8h, after the reaction is completed, washing, and freeze-drying to obtain composite carbon nanotubes; S4: PET resin, composite carbon nanotubes, surfactant and coupling agent are uniformly mixed to obtain a composite material, and after standing for 8-12 hours, the composite material is melt-extruded, cast, cast and biaxially stretched to obtain a PET base film.
4. A functional current collector according to claim 3, characterized in that: In step S1, the reaction mass ratio of the pretreated carbon nanotubes and thionyl chloride is (0.5-0.7):
65.
5. A functional current collector according to claim 3, characterized in that: In step S2, the contents of the modified carbon nanotube components are: by mass: 20-25 parts of chlorinated carbon nanotubes, 3-4 parts of silicon polymer, 100-150 parts of 1,4-dioxane, 10-14 parts of polyethylene terephthalate, 5-6 parts of 1,2-dichloroethane, and 5-6 parts of trifluoroacetic acid.
6. A functional current collector according to claim 5, characterized in that: The preparation process of silicon polymer is as follows: sodium hydroxide powder and deionized water are mixed, ultrasonically dispersed for 30-40 minutes, silicon dioxide powder is added to react for 3-4 hours, 35-38% hydrochloric acid solution, tetrahydrofuran and sodium chloride are added, and the reaction is continued for 30-40 minutes. After the reaction is completed, the organic layer is allowed to stand for dehydration, suction filtration and distillation to obtain silicon polymer; the content of each component of the silicon polymer is: in parts by mass, 1.0-1.2 parts of sodium hydroxide powder, 60-70 parts of deionized water, 3.0-3.5 parts of silicon dioxide powder, 65-70 parts of hydrochloric acid solution, 160-180 parts of tetrahydrofuran and 36-40 parts of sodium chloride.
7. A functional current collector according to claim 3, characterized in that: In step S3, when preparing the aminated carbon nanotubes, the reaction mass ratio of the main reactants, the modified carbon nanotubes and oxycarbonyl-4-hydroxyaniline, is 4:(1.0-1.5).
8. A functional current collector according to claim 3, characterized in that: In step S3, the reaction mass ratio of the amination carbon nanotubes, the aniline monomer and the ammonium persulfate is (0.02-0.03):6:
3.
9. A functional current collector according to claim 3, characterized in that: In step S4, the contents of the components of the composite material are: by mass, 75-85 parts of PET resin, 20-30 parts of composite carbon nanotubes, 0.5-0.7 parts of surfactant, and 0.5-0.7 parts of coupling agent; the surfactant is sodium dodecylbenzene sulfonate, and the coupling agent is γ-aminopropyltriethoxysilane.
10. A method for guiding a functional current collector, characterized in that: The following steps are involved: A lithium-ion battery prepared using the functional current collector according to any one of claims 1 to 9, comprising the following steps: assembling a positive electrode current collector and a positive electrode active material layer into a positive electrode, assembling a functional current collector and a negative electrode active material layer into a negative electrode, assembling the positive electrode and the negative electrode into a battery, then selecting an aluminum-plastic film shell for packaging and molding, and performing electrolyte injection, aging, formation, and volume separation to obtain a lithium-ion battery.
Citation Information
Cited By
Conductive slurry for positive electrode of lithium ion battery
CN120089746A
Negative current collector and preparation method thereof, pole piece and battery
CN120709380A